2021
DOI: 10.1101/2021.03.21.436353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An epigenome atlas of neural progenitors within the embryonic mouse forebrain

Abstract: While epigenetic modifications are critical for cell state changes throughout development, a detailed characterization of chromatin accessibility during neurogenesis has not been explored. We collected single-cell chromatin accessibility profiles from four distinct neurogenic regions of the embryonic mouse forebrain using single nuclei ATAC-Seq (snATAC-Seq). We identified thousands of differentially accessible peaks, many restricted to distinct progenitor cell types or brain regions. Integrating snATAC-Seq and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 146 publications
(194 reference statements)
1
5
0
Order By: Relevance
“…To select enhancers with activity in the developing forebrain, we intersected MEIS1/2-DLX5 co-binding sites from ChIP-seq data with the VISTA in vivo enhancer database (Visel et al, 2007) (Figure S3d). Additionally, we confirmed the accessibility of respective genomic regions utilizing published scATAC-seq data of the LGE and MGE (Rhodes et al, 2022) (Figure 4a). We chose two enhancers (hs1080 and hs956) of the transcription factor Foxp2 , which both contained MEIS/DLX motifs with a spacing of 3 bps (Visel et al, 2007; Visel et al, 2013) (Figure 4a, Figure S4a-c,e).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…To select enhancers with activity in the developing forebrain, we intersected MEIS1/2-DLX5 co-binding sites from ChIP-seq data with the VISTA in vivo enhancer database (Visel et al, 2007) (Figure S3d). Additionally, we confirmed the accessibility of respective genomic regions utilizing published scATAC-seq data of the LGE and MGE (Rhodes et al, 2022) (Figure 4a). We chose two enhancers (hs1080 and hs956) of the transcription factor Foxp2 , which both contained MEIS/DLX motifs with a spacing of 3 bps (Visel et al, 2007; Visel et al, 2013) (Figure 4a, Figure S4a-c,e).…”
Section: Resultssupporting
confidence: 75%
“… a , Representative profiles of MEIS1/2 (red) and DLX5 (blue) ChIP-Seq at E14.5 and E13.5 respectively, as well as scATAC-seq from LGE (dark grey) and MGE (grey) at E12.5 are shown at the Foxp2 gene locus. DLX5 ChIP-Seq data from (Lindtner et al, 2019); scATAC-seq data from (Rhodes et al, 2022). b , Luciferase activity driven by the enhancer hs1080, co-transfected with Meis2 and Dlx5 expression vectors in Neuro2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B ) and identified 3238 common peaks from three biological replicates. We then manually inspected the 31 gene loci for PRDM16 CUT&TAG peaks pairing with the target gene TSS using the browser Embryonic Mouse Brain Epigenome Atlas (Rhodes et al, 2022). This conformed that most of these genes have at least one PRDM16 binding peak in their promoter-linked enhancers (Text in black, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that PRDM16 preferentially associates with distal intergenic regions (He et al, 2021), posing a challenge of pairing the PRDM16-bound enhancers to the targeting promoters. To overcome this issue, we took advantage of a public data browser, Embryonic Mouse Brain Epigenome Atlas (Rhodes et al, 2022), where promoterenhancer pairs are predicted by the Monocle3 extension Cicero (Pliner et al, 2018). We manually inspected all 31 genes for the presence of at least one PRDM16 CUT&TAG peak that is associated with the gene promoter, and found that 23 of them have proximal or distal PRDM16 binding peak(s) (Fig.…”
Section: Genomic Relocation Of Smad4/psmad De-represses Cell Prolifer...mentioning
confidence: 99%